Is safety a subject for science? - Hollnagel, Erik (Safety science, 2014)
•The paper addresses the meaning of safety as a scientific subject.•Conventionally, safety is defined by what happens when it is absent.•But to make sense, safety should be defined by what happens when it is present.•Safety science should therefore focus on situations where nothing goes wrong. In this paper I will not so much address the status of safety science as a science, but rather address the status or meaning of safety. So instead of entering into a discussion of whether safety science is a proper science – whatever that means – the focus will be on whether the notion of safety itself is a proper subject for scientific investigation or indeed whether safety as such is an appropriate topic or subject for a scientific discipline.